Influences of Interaction Styles and Its Relation to Bloom’s Taxonomy on Level 3 Thinking Skills for Children at age 8-9 in Educational Application (Case Studies: Math Subject) - Veronikha Effendy; Mira Kania Sabariah; Junaedi, Danang; Arbi Baruni (International Journal on Information and Communication Technology (IJoICT), 2024)
Educational application is one of the supplementary learning processes that help children to develop their thinking skills. One of the thinking skills is called application or third level (C3 level) in Bloom's Taxonomy for children aged 8 to 9 years. To help those children develop thinking skills, an educational application needs interaction styles to support and bear children in the learning process. The method to determine which interaction styles best suit children's C3 level thinking skills is by comparing two styles. The conclusion from the tests that have been carried out and the data generated for children aged 8-9 years is that the interaction style is form-filling. This interaction style had higher results and preferences in all three tests than the Direct Manipulation interaction style. Children had shorter average processing times, higher average scores, and preferred questions with the form-filling interaction style